Match running performance is influenced by possession and team formation in an English Premier League team - Morgans, Ryland; Radnor, John; Fonseca, Jose; Haslam, Chris; King, Matthew; Rhodes, Dave; Żmijewski, Piotr; Oliveira, Rafael (Biology of Sport, 2024)
The aim of this study was to examine the possession (very low, low, high, and very high), team formation (3-5-2 and 4-3-3) and position (centre-backs, full-backs, centre midfielders, attacking midfielders, and centre forwards) on match load across two consecutive seasons in elite soccer. Twenty-seven English Premier League outfield players were recruited. Data was monitored through an 18 Hz Global Positioning System and a 25 Hz semi-automated camera tracking system, respectively, and all variables were analysed per minute. Main effects for formation on total distance (TD) ( p = 0.006; η 2 = 0.010), high-speed running (HSR) ( p = 0.009; η 2 = 0.009), number of high metabolic load (HML) efforts ( p = 0.004; η 2 = 0.011) were observed. In addition, there were significant interaction effects with formation×possession on TD ( p < 0.001; η 2 = 0.043), HSR ( p = 0.006; η 2 = 0.018), sprinting ( p < 0.001; η 2 = 0.030), HML efforts ( p < 0.001; η 2 = 0.035), accelerations ( p < 0.001; η 2 = 0.025). From the position specific analysis, only the running performance of centre-backs was affected by formation or positional factors. These results indicate that formation and possession can have a significant impact on TD, HSR, and HML distance. Furthermore, players performed more high intensity efforts in 3-5-2 than 4-3-3 formation. These findings suggest that coaches can evaluate running performance in the context of formation and possession and tailor tactical strategies to optimise physical performance.